2021
DOI: 10.1016/j.pld.2020.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Fossil fruits of Firmiana and Tilia from the middle Miocene of South Korea and the efficacy of the Bering land bridge for the migration of mesothermal plants

Abstract: Determining whether the high-latitude Bering land bridge (BLB) was ecologically suitable for the migration of mesothermal plants is significant for Holarctic phytogeographic inferences. Paleobotanical studies provide a critical source of data on the latitudinal positions of different plant lineages at different times, permitting assessment of the efficacy of the BLB for migration. Here we report exceptionally preserved fossils of Firmiana and Tilia endochrysea from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Despite these previous findings of Firmiana and Craigia fossils, especially in East Asia (Xie et al, 2014; Jia et al, 2021; Wang et al, 2021a), no occurrence has been reported from what is now the Tibetan Plateau. The Tibetan Plateau, also called the “Third Pole” of the world (Qiu, 2008), is the highest plateau worldwide.…”
Section: Introductionmentioning
confidence: 84%
See 4 more Smart Citations
“…Despite these previous findings of Firmiana and Craigia fossils, especially in East Asia (Xie et al, 2014; Jia et al, 2021; Wang et al, 2021a), no occurrence has been reported from what is now the Tibetan Plateau. The Tibetan Plateau, also called the “Third Pole” of the world (Qiu, 2008), is the highest plateau worldwide.…”
Section: Introductionmentioning
confidence: 84%
“…Because the specimens studied here are fin-winged fruits, we follow the venation terminology developed previously for leaves (Ellis, 2009), as well as terminology in prior relevant literature relating to these types of fruit (Manchester & O'Leary, 2010;Jia et al, 2021;Wang et al, 2021a). Initial comparisons were made with existing literature describing fin-winged fruits (Manchester & O'Leary, 2010) and herbarium sheets consulted online (Appendix I), including the Queensland Department of Environment and Science (2020), the New York Botanical Garden (NYBG), the National Herbarium of the Netherland (NHN), the Muséum National d'Histoire Naturelle, Herbier National (P), the Harvard University Herbaria (HUH), the Kew Herbarium (K), the Guangxi Institute of Botany (IBK) and the Chinese National Herbarium (PE).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations